2012
DOI: 10.1111/ene.12053
|View full text |Cite
|
Sign up to set email alerts
|

The effects of multidisciplinary rehabilitation in patients with early‐to‐middle‐stage Huntington's disease: a pilot study

Abstract: This pilot study suggests that a prolonged multidisciplinary rehabilitation programme in early-to-middle-stage HD is feasible, well-tolerated and associated with therapeutic benefit. Further explorative, larger studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
2
17

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 9 publications
6
82
2
17
Order By: Relevance
“…Eighteen patients with manifest HD (11 men, 7 women) were recruited using the Huntington’s Enrichment Research Optimisation scheme database [12], with assistance from the Huntington’s Western Australia Association. Inclusion criteria were a positive genetic test, clinically verified disease expression (Unified Huntington’s Disease Rating Scale–Total Motor Score [UHDRS-TMS] ≥5), and the ability to understand and respond to instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Eighteen patients with manifest HD (11 men, 7 women) were recruited using the Huntington’s Enrichment Research Optimisation scheme database [12], with assistance from the Huntington’s Western Australia Association. Inclusion criteria were a positive genetic test, clinically verified disease expression (Unified Huntington’s Disease Rating Scale–Total Motor Score [UHDRS-TMS] ≥5), and the ability to understand and respond to instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Studies evaluating the utility of multidisciplinary therapy have documented significant changes in grey matter volume, as well as improvements in memory, processing speed, balance and gait, mood and quality of life in patients with manifest HD (144)(145)(146)(147). Recent data from our research programme has shown, in particular, that multidisciplinary therapy increases grey matter volume in the caudate tail and dorsolateral PFC in patients with manifest HD (147).…”
Section: Effects Of Multidisciplinary Therapy On Brain Volume and Potmentioning
confidence: 99%
“…To date, rehabilitation studies of early-to-moderate stage HD have focused on improving motor functions such as gait and balance [1013]. An exploratory study on the effects of multi-disciplinary rehabilitation on brain structure and cognition showed increased gray matter volume that corresponded with significant improvements in verbal learning and memory [14].…”
Section: Introductionmentioning
confidence: 99%